The use of the ABC classification for prioritization in inventory management: a case study in a company in the stationery sector - Vitorino, Lucas Eduardo Draprinchinski; Mendonça, Anny Key de Souza (Brazilian Journal of Production Engineering, 2022)
With the growing need to remain competitive in the market, companies seek a correct control and management of their stock, so that this becomes a differential with respect to competitors. This research aims to use the ABC Classification to prioritize items to determine stock control parameters such as minimum stock, order point, maximum stock and the economic purchase lot in a company in the stationery sector. Seeking to identify possible fields of improvement in the company’s current form of inventory management, the ABC Classification method was used to determine which products should have greater focus and attention in relation to products that are not so significant for the company. The results show that when applying the ABC Classification on the items in stock, it was observed that five items represent 70.82% of the total stock value, where these products were considered classified as A, seven items classified as B and represent 19.68% of the stock value and eighteen items represent 9.5% of the total value of the stock and classified as C. When performing out the study regarding the stock control parameters, it was found that the item A09 presents a purchased lot currently created by the company above the necessary, inconsequently, this generates a high amount of capital invested needlessly, as the quantity in stock of this product is extremely high compared to the value of its monthly demand. Thus, it is concluded that correct prioritization of the stock of items can prevent the unduly use of capital as well as reduce costs with storage and movement of these products in stock.